Pengaruh Audit Delay dan Financial Distress Terhadap Auditor Switching (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di BEI Tahun 2021-2024) - Nur Habibah; Indupurnahayu .; M. Anwar Masruri (CV. ITTC INDONESIA, 2026)
Auditor Switching is an important issue in auditing because it is closely related to auditor independence and the quality of corporate financial reporting. A company’s decision to change its auditor may be influenced by several factors, including Audit Delay and Financial Distress. The inconsistent findings of previous studies indicate the existence of a research gap that requires further investigation, particularly in Consumer Cyclicals companies listed on the Indonesia Stock Exchange (IDX). This study aims to examine the effect of Audit Delay and Financial Distress on Auditor Switching, both partially and simultaneously, in Consumer Cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research employed a quantitative approach with a causal associative design. The population consisted of 164 Consumer Cyclicals companies listed on the Indonesia Stock Exchange during 2021–2024. The sample was selected using purposive sampling, resulting in 29 companies with a total of 116 observations. Secondary data in the form of audited financial statements and annual reports were collected from the official Indonesia Stock Exchange website and company websites. Data collection was conducted through documentation techniques, while data analysis was performed using logistic regression with SPSS software. The results indicate that Audit Delay has a positive and significant effect on Auditor Switching with a significance value of 0.044 (<0.05). Financial Distress does not have a significant effect on Auditor Switching with a significance value of 0.315 (>0.05). Simultaneously, Audit Delay and Financial Distress significantly affect Auditor Switching with a significance value of 0.013 (<0.05). This study concludes that longer audit completion periods increase the likelihood of auditor switching, whereas Financial Distress is not a primary determinant of such decisions. The findings imply that companies should improve audit timeliness to maintain financial reporting quality and reduce the likelihood of auditor switching.